(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Light Fidelity (Li-Fi) is a label for wireless-communication systems using light as a carrier instead of traditional radio Frequencies [1], as in Wi-Fi. Li-Fi has the advantage of being able to be used in sensitive areas such as in Aircraft without causing interference. However, the light waves used cannot penetrate walls. It is typically implemented using white LED light bulbs at the Downlink transmitter. The operational procedure is very simple-, if the LED is on, you transmit a digital 1, if it’s off you transmit a 0. The LEDs can be switched on and off very quickly, which gives nice opportunities for transmitting data. Hence all that is required is some LEDs and a controller that code data into those LEDs. All one has to do is to vary the rate at which the LED’s flicker [2] depending upon the data we want to encode. Li-Fi can be useful in future as a replacement and backup of Wireless Fidelity (Wi-Fi) for indoor communication because it can provide high data rate of transmission along with high capacity to utilize more users as its spectrum bandwidth is much broader than the radio spectrum. In this paper we will look at the different aspects of the Li-Fi based indoor communication system, summarizes some of the research conducted so far and we will also proposed a Li-Fi based communication model keeping in mind coverage area for multiple user and evaluate its performance under different scenarios. Such advancements promise a theoretical speed of 10 Gbps-meaning one can download a full high-definition film in just 30 seconds.